Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
-0.832 m/s²
Explanation:
Since acceleration a = (v - u)/t where u = initial velocity of astronaut = +14.7 m/s (positive since he is moving towards the right), v = final velocity of astronaut = +4.8 m/s (positive since he is moving towards the right) and t = time taken for velocity change = time interval = 11.9 s.
Since a = (v - u)/t
Substituting the values of the variables into the equation, we have
a = (v - u)/t
a = (+4.8 m/s - (+14.7 m/s))/11.9 s
a = (4.8 m/s - 14.7 m/s)/11.9 s
a = -9.9 m/s ÷ 11.9 s
a = -0.832 m/s²
So, the astronaut's average acceleration is -0.832 m/s²
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.